ANALISIS KESELARASAN TEORI NEURO LINGUISTIC PROGRAMMING RICHARD BANDLER DENGAN KONSEP MANACIKA PARISUDHA - Permana, I Dewa Gede Darma (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
The mind is the distinguishing element that makes humans called rational beings. But in reality, an uncontrolled mind can also bring big problems to human life. This is what led Richard Bandler to create the theory of Neuro Linguistic Programming (NLP) to help humans control their minds. The same thing is also provided by the concept of Manacika Parisudha, as a guideline for mind control teachings from the Hindu perspective. On this basis, researchers are interested in studying both by using NLP theory as an analysis knife in the concept of Manacika Parisudha. By using the philosophical hermeneutic method, and through the Miles and Huberman interactive analysis pattern, the results of this study show that: 1). NLP theory by Richard Bandler as a theory, method, technique, or science that discusses the human mind, the language used, and human behavior as a rational individual in an effort to meet needs. 2). The concept of Manacika Parisudha is a concept of good, holy, and right thinking according to Hinduism. 3). In terms of analysis, there are some similarities between the NLP theory and the concept of Manacika Parisudha in terms of mind control.